2015
DOI: 10.3390/ijms161226076
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogenicity-Related Genes in Biofilm-Defective Acidovorax citrulli by Transposon Tn5 Mutagenesis

Abstract: Biofilm formation is important for virulence of a large number of plant pathogenic bacteria. Indeed, some virulence genes have been found to be involved in the formation of biofilm in bacterial fruit blotch pathogen Acidovorax citrulli. However, some virulent strains of A. citrulli were unable to format biofilm, indicating the complexity between biofilm formation and virulence. In this study, virulence-related genes were identified in the biofilm-defective strain A1 of A. citrulli by using Tn5 insertion, patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…For example, Bahar et al (2011) reported that the fliC mutant of A. citrulli, which is involved in swimming motility, showed a significant reduction in virulence in seed transmission assays and stem and foliage inoculations, compared to the wild-type. Consistently, Luo reported that a biofilm-defective A. citrulli mutant showed reduced virulence [34]. Additionally, Wang et al [28] also reported that swimming motility and biofilm formation were important for the virulence of A. citrulli.…”
Section: Discussionmentioning
confidence: 79%
“…For example, Bahar et al (2011) reported that the fliC mutant of A. citrulli, which is involved in swimming motility, showed a significant reduction in virulence in seed transmission assays and stem and foliage inoculations, compared to the wild-type. Consistently, Luo reported that a biofilm-defective A. citrulli mutant showed reduced virulence [34]. Additionally, Wang et al [28] also reported that swimming motility and biofilm formation were important for the virulence of A. citrulli.…”
Section: Discussionmentioning
confidence: 79%
“…It has been well known that biofilm formation is a dynamic and complex process involving signal transduction systems, transcriptional regulation, and stress response, which make it important for both beneficial bacteria and plant pathogenic bacteria [ 15 , 35 ]. In agreement with the results from some other studies, most of the mutants significantly reduced biofilm formation, which may, at least partially, be attributed to the reduced antifungal activity against R. solani .…”
Section: Resultsmentioning
confidence: 99%
“…A library of Tn5 transposon mutants of B. seminalis R456 was constructed using the MA138E-EZ-Tn5-KAN-2 TNP Transposome Kit, which was carried out according to the manufacturer’s protocol (Epicentre Biotechnologies, Madison, WI, USA). The competent cells and electroporation transformation were prepared using a previously described method [ 15 ] with slight modifications. In brief, following precooling for 40 min, bacterial cells were suspended in 40 μL sterile water to obtain a final concentration of 1 × 10 10 CFU/mL, and then added to 1 μL of the EZ-Tn5 transposon (Epicentre Biotechnologies, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations